Association of the TNF‐α‐308G>A gene polymorphism with left ventricular geometry and functional abnormalities in obstructive sleep apnea subjects - Chen, Shuqiong; Wang, Jian; Shui, Wen; Xing, Xueqing; Zhang, Zhenxia; Hou, Ran (Journal of clinical ultrasound, 2024)
Objective Tumor necrosis factor‐α (TNF‐α) can induce left ventricular remodeling. In this study, we investigated whether the TNF‐α‐308G>A polymorphism is associated with left ventricular geometry (LVG) and left ventricular functional abnormalities in obstructive sleep apnea (OSA) subjects. Methods Two hundred and seventy‐eight subjects were enrolled. Echocardiography and genetic data were assessed in all patients. Geometric patterns of the left ventricle were determined from the relative wall thickness and left ventricular mass index (LVMI). Genetic analysis for the TNF‐α‐308G>A SNP rs1800629 was identified by Sanger sequencing. The correlations of the TNF‐α‐308G>A polymorphism with LVG and left ventricular function were analyzed by difference analysis and logistic regression. Results The chi‐square test showed that there were differences in genotype distributions among the four groups (p = 0.033), such that the frequency of GA+AA genotypes was significantly higher in the concentric hypertrophy group than in the normal geometry group (p < 0.05). Independent sample T tests showed that the GA+AA genotypes had higher IVST, LVPWT, LVMI, E/e' values, and lower e' values than those of the GG genotype (p < 0.05). Logistic regression analysis showed that the TNF‐α‐308G>A polymorphism was independently correlated with eccentric hypertrophy (OR = 2.456, p = 0.047) and concentric hypertrophy (OR = 2.456, p = 0.047). Conclusion In OSA patients, the TNF‐α‐308G>A polymorphism was linked to LVG and abnormal left ventricular diastolic function, suggesting that the TNF‐α‐308G>A polymorphism may have an important influence on LVG alterations. In this study, we used echocardiography, including the latest autoSTRAIN technology, to evaluate left ventricular structure and function and found that TNF‐α‐308G>A polymorphism was correlated with the hypertrophic LVG (concentric hypertrophy and eccentric hypertrophy) and left ventricular diastolic function.